Improving Numeracy Literacy Through the Integration of Challenge Based on Differentiated Learning with STEAM Based Website - Ananda Verry Setiawan; Stefany Margaretha Hutauruk; Selva Ayu Meilina; Adi Satrio Ardiansyah (Universitas Negeri Semarang, 2024)
Numeracy literacy is essential for 21st-century skills, yet student proficiency remains low. Improving it requires enhancing learning quality through digital innovation, contextual learning, and personalized approaches. Digital platforms offer flexible resources, while STEAM disciplines foster problem-solving skills. Challenge-Based Learning (CBL) provides contextual, project-oriented experiences, supported by differentiation strategies (visual, auditory, kinesthetic). The purpose of this research is to develop a STEAM-based website integrated with challenges based on differentiated learning which is very valid and very practical to improve students' numeracy literacy. This research method used Research and Development (R&D) method with ADDIE model, the research involved junior high students, collecting data via interviews and questionnaires. Results showed product is very valid (89.95% expert validation) and very practical (93.80% from practitioners, 93.16% from students). Thus, differentiated, CBL-STEAM learning can significantly improve learning quality and support broader educational goals.